2011
DOI: 10.1007/s00347-010-2284-7
|View full text |Cite
|
Sign up to set email alerts
|

Komplikationen nach kosmetischer Irisimplantation

Abstract: We report the case of a 37-year-old patient with ocular complications associated with the implantation of cosmetic iris implants. Implantation of silicone iris implants for the purpose of changing iris colour has been performed since 2004. Diaphragms are implanted in the anterior chamber. Up to now only little information exists about side effects of this method. In the literature severe ocular complications shortly after cosmetic iris implantation are reported in single cases. In our case 5 months after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…According to our experience, a diameter of 11 mm after trephination is suitable for most eyes. This might be the reason why we did not see a significant increase of IOP after artificial iris implantation compared to previous studies [6]. Mayer et al also recommend a smaller diameter and achieved a low complication rate with glaucoma [16].…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…According to our experience, a diameter of 11 mm after trephination is suitable for most eyes. This might be the reason why we did not see a significant increase of IOP after artificial iris implantation compared to previous studies [6]. Mayer et al also recommend a smaller diameter and achieved a low complication rate with glaucoma [16].…”
Section: Discussioncontrasting
confidence: 58%
“…A severe complication after artificial iris implantation is glaucoma [6]. In this study, 9 % developed glaucoma after implantation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Clinical examination in our series of 14 eyes confirmed multiple complications from these implants, including increased IOP, pigment dispersion, uveitis, corneal edema, a depressed ECC, UGH syndrome, glaucomatous optic neuropathy, CME, and suprachoroidal hemorrhage.…”
Section: Discussionmentioning
confidence: 72%
“…These complications include severe vision loss, uveitis-glaucoma-hyphema (UGH) syndrome, elevated intraocular pressure (IOP), endothelial cell loss, bullous keratopathy, and end-stage glaucomatous optic neuropathy. [5][6][7][8][9][10] However, information on the long-term management and visual outcomes of these patients is lacking. George et al 8 reported through a personal communication with Kahn Medical in 2001 that more than 700 procedures had been performed since 2002, with an incidence of chronic inflammation of 1.5% and an occurrence of raised IOP that could be adequately controlled with eyedrops.…”
mentioning
confidence: 98%